STRUCTURE MODELING OF VRK1 PROTEIN AND ITS MOLECULAR DOCKING STUDY WITH RIBAVIRIN ANALOGS - SHANKARACHARYA; BHAVANA SRIVASTAVA; AMBARISH S. VIDYARTHI (International Journal of Pharma and Bio Sciences, 2010)
In order to design better drug for the treatment of Hepatitis C Virus, a 3-D model of the Vaccine Related Kinase 1 protein was generated based on the crystal structure of the Vaccine Related Kinase 2 (PDB ID 2V62) having 57% sequence identity. The two sequences were also aligned with a third protein VRK 3 (2JII) to see the similarity between the three. Its 3-D structure was evaluated and validated using PROCHECK comprising 97.5% amino acid residues in favored and additional allowed region of Ramachandran plot. The model was also validated with What_check and Errat, which confirms that the model was of good quality. With this model, a docking study was performed with GLIDE using 93 analogs of Ribavirin and the results indicated that the ASN377, PRO190, SER136, LYS392, THR390 and SER376 form hydrogen bonds and have strong nonbonding interaction with the analog CID_196553. This finding may help to understand the nature of VRK1 and development of specific anti-HCV therapies. Our results may be helpful for further experimental investigations.